Feiras especiais e o consumidor: a experiência da junta local - Castro, Thais Monteiro de (2018)
The current dissertation intends to present the conception and operation of Junta Local, a special street fair, one that tries to handle the ciculation and consumption of gastronomic, rural and organic itens, produced by small manufacturers. This is a initiative that claims to practice the fair trade in a engaged community constituted of small rural and urban producers, locals of the city of Rio de Janeiro. In analyzing this experience, was pursued to identify the concepts and principles that rule it´s organization, creating a counterpoint with similar experiences. Utilizing interviews with the founders, producers of the network and consumers of the fair, this research analyzes concepts and discourses widespread by the group, introducing the profile of both consumer and producer and its bond with the notions spread by Junta Local.